Pengaruh Pendidikan Kursus Evangelisasi Pribadi Terhadap Perilaku Mengasihi Dalam Keluarga - Benedektus Nugroho Susanto (Sekolah Tinggi Filsafat Seminari Pineleng, 2021)
The article discusses the finding of the research on the effects of Personal Evangelization Classes. The author attempts to find out the connection of the personal evangelization classes with the effort to develop a loving behavior within the family as a way of testifying or evangelizing. The methods employed in the project are mixed, both qualitative and quantitative. The research shows that attendants’s understanding from the courses inspires them to spread out the word of God to others. One effort of their evangelization is by giving examples through their own daily life. They practice good behaviors in their family life and daily practices in form of loving behaviors within their family. The Christian family may grow and be able to participate in the church and society actively.